P.112 Mechanical properties of fusiform aneurysms in a rabbit model. (17th June 2016) - Altamimi, M; Meek, C; Di Martino, E; Mitha, A
Abstract : Background: Animal models of human cerebral aneurysms have been a vital part of the development of endovascular treatments for decades. Rabbit models have been successfully used to simulate the morphology and hemodynamics of human intracranial aneurysms. However, the lack of mechanical testing of human intracranial aneurysm tissue limits our understanding of the mechanisms of aneurysm rupture. The goal of this project is to develop techniques for the mechanical testing of fusiform aneurysms in a rabbit model.Methods: Fusiform aneurysms were created using the right carotid artery using an elastase-based method. Thirty fusiform aneurysms and healthy rabbit carotid artery samples were then collected from our lab and tested with a uniaxial and biaxial loading system. Rectangular strips of aneurysm and healthy tissue were obtained in the axial and circumferential direction with a micro-cutting instrument. The test samples were gripped by a custom-designed micro-clamp and placed in a bath of phosphate-buffered saline at 37˚C temperature.Results: Maximum stress of healthy and aneurysm arteries are 50 Kpa and 0.6 KpaConclusions: The strength of healthy tissue was significantly higher than tissue from the fusiform aneurysm. These techniques will provide us with strategies for the eventual testing of human intracranial tissue and may help us to understand mechanisms of aneurysm rupture.